Psyched Up or Psyched Out? The Influence of Coactor Status on Individual Performance - Flynn, Francis J.; Amanatullah, Emily T. (Organization Science, 2012)
We propose that performing an independent task alongside a coactor who is an outstanding performer will improve a focal actor's performance. In three studies that ranged from laboratory participants solving anagrams and playing video games to professional golfers competing in the Masters Tournament, performance improved more in the presence of a high-performing coactor than in the presence of a weak-performing coactor. However, when people were asked to compete directly with a strong performer, their own performance declined. In sum, when faced with the anxiety of performing alongside a high-status coactor, independent coaction led people to become “psyched up,” whereas direct competition led them to become “psyched out.”